DEVELOPMENT OF AN ATLAS WITH CONTEXTUAL ILLUSTRATIONS OF FISH TYPES FOR ANIMALIA STUDIES IN GRADE X SMA/MA - Nurhadi, Nurhadi; Nugraheni, Putri Sagita; Zural, Mimin Mardhiah (BioCONCETTA, 2023)
The purpose of this research is to develop a Pisces Atlas with contextual nuances for Grade X SMA/MA students using the Plomp Model. Contextual nuances are obtained by collecting and documenting fish commonly consumed or kept by the people of West Sumatra. The validity test was evaluated by 3 expert lecturers. The feasibility test was assessed through one-to-one (3 students) and small group (6 students) evaluations. The instrument used was a questionnaire with a Likert Scale, processed using percentage formulas, and analyzed descriptively. The fish sampling technique for the atlas was conducted through a survey method, documenting fish in traditional markets and fish auctions in Padang City and Dharmasraya Regency, West Sumatra. The identified fish were used as teaching materials for Animalia topics, focusing on Pisces, in the form of an Atlas. The atlas received very valid validity test results (89.15%), and very feasible one-to-one and small group test results (90% and 93.05%). Therefore, the developed Pisces atlas can be used for teaching in Grade X SMA/MA.